موقف علماء النصارى المعاصرين من محمد صلى الله عليه وسلم والرد عليهم "أنيس شوروش وزكريا بطرس أنموذجا" - Abdelhamed Ibrahim Abdullah Sultan
This research study focuses on "the attitude of the contemporary Christian scholars about the prophet Mohammad (peace be upon him) with a respond to their suspicions", Anis Shorrosh, and Zakaria Boutros as models (Case Studies). The study gives an answer to the main query: what is the motivation behind the attitude of some Christians being aggressive against the Prophet of Islam, though his prophecy had been proven in their holy books? The study aims to follow the tidings of the Prophet of Islam in the sources of Jews and Christians and explaining them. Then we introduce Anis Shorrosh and Zakaria Boutros, clarify the main suspicions that they provoke about denying Mohammad's prophecy with our respond to those suspicions. We also show their attitude about the revelation and the revelation of the Qur'an. Lastly, we highlight the most important suspicions that they provoke about the Prophet's polygamy and how he used to treat his wives. The researcher has followed the critical analytical approach, and historical inductive approach. The results that have been reached are: there is a relevant relation between the modern Christians' attitude and their antecedents toward the Prophet Mohammad (peace be upon him), besides the existence of a contradiction in the measures of the freedom of opinion and expression in the Christian world; for instant, while they allow insulting the Prophet of Islam (peace be upon him), this is completely forbidden when it comes to the Semitism. Another result is that one of the vital reasons of Zakareya's attitude against the Islam, and Muslims in general, is the death of his brother who was killed in Egypt by the Muslim Brothers "Ikhwan" in 9 f A because of his missionary work. The goal of publishing Zakaria Boutros's book "The True Furqan" is to convert Muslims into Christians, and stable the Christianity and to consider that the message of Isa (Jesus) is the last message. The conclusion of this study includes the following suggestions and recommendations: among them the need to use the dialogue in dealing with others, and advocacy with wisdom and good advices, and arguing in a good way not by violence, bombings and killing of innocent people. Also, teaching such suspicions in the university and postgraduate levels is very important in order to clarify, them and protect our youths from such confusions.